Quantification of tumor induced motor cortical plasticity using navigated transcranial magnetic stimulation in patients with adult-type diffuse gliomas - Almeida, Cesar Cimonari de; Neville, Iuri Santana; Hayashi, Cintya Yukie; Gomes dos Santos, Alexandra; Brunoni, André Russowsky; Teixeira, Manoel Jacobsen; Paiva, Wellingson Silva (Frontiers in Neuroscience, 2023)
Introduction The evaluation of brain plasticity can provide relevant information for the surgical planning of patients with brain tumors, especially when it comes to intrinsic lesions such as gliomas. Neuronavigated transcranial magnetic stimulation (nTMS) is a non-invasive tool capable of providing information about the functional map of the cerebral cortex. Although nTMS presents a good correlation with invasive intraoperative techniques, the measurement of plasticity still needs standardization. The present study evaluated objective and graphic parameters in the quantification and qualification of brain plasticity in adult patients with gliomas in the vicinity of the motor area. Methods This is a prospective observational study that included 35 patients with a radiological diagnosis of glioma who underwent standard surgical treatment. nTMS was performed with a focus on the motor area of the upper limbs in both the affected and healthy cerebral hemispheres in all patients to obtain data on motor thresholds (MT) and graphical evaluation by three-dimensional reconstruction and mathematical analysis of parameters related to the location and displacement of the motor centers of gravity (ΔL), dispersion (SDpc) and variability (VCpc) of the points where there was a positive motor response. Data were compared according to the ratios between the hemispheres of each patient and stratified according to the final pathology diagnosis. Results The final sample consisted of 14 patients with a radiological diagnosis of low-grade glioma (LGG), of which 11 were consistent with the final pathology diagnosis. The normalized interhemispheric ratios of ΔL, SDpc, VCpc, and MT were significantly relevant for the quantification of plasticity (p < 0.001). The graphic reconstruction allows the qualitative evaluation of this plasticity. Conclusion The nTMS was able to quantitatively and qualitatively demonstrate the occurrence of brain plasticity induced by an intrinsic brain tumor. The graphic evaluation allowed the observation of useful characteristics for the operative planning, while the mathematical analysis made it possible to quantify the magnitude of the plasticity.